PENGARUH PUPUK KANDANG SAPI DAN PUPUK NPK TERHADAP PERTUMBUHAN DAN HASIL SAWI PADA TANAH ALUVIAL - Juanda, Juanda; Zulfita, Dwi; Maulidi, Maulidi (Fakultas Pertanian Universitas Tanjungpura, 2025)
The goal of this study was to examine the effect of the interaction between cowmanure and NPK fertilizer on the growth and yield of mustard greens on alluvial soil.This research was conducted from April 30th to May 30th, 2022, on Perdamaian street, Parit Banjar, Melati Hamlet, Kalimas Village, Sungai Kakap District, Kubu Raya Regency. The method of this study was Completely Randomized Design (CRD) with 2 treatment factors including cow manure (s) and NPK fertilizer (n) with 3 repetition of 4 sample plants so that there were 108 plants. The treatment factors in the research include; the doses of cow manure consisting of 3 levels, s1 = 10 tons/ha, s2 = 20 tons/ha, s3 = 30 tons/ha, and the doses of NPK fertilizer consisting of 3 levels, n1 = 250 kg/ha , n2 = 300 kg/ha, n3 = 350 kg/ha. The variables observed in this study were the root volume, leaves chlorophyll content, plant dry weight, number of leaves, leaf area and plant fresh weight. Based on the results of the research that has been successfully conducted, it can be concluded that cow manure at the dose of 30 tons/ha + NPK fertilizer at the dose of 350 kg/ha is the best dose for increasing the number of leaves of mustard greens on alluvial soil.